KENDALA DAN TANTANGAN PENDIDIKAN BERBASIS TEKNOLOGI (TECHNOLOGY-BASED CONSTRAINTS AND EDUCATIONAL CHALLENGES) - Munawir, M; Apriana, Enika Dwi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Education will develop more and more, of course, supported by the existence of information and communication technology so that it becomes digital education that can support the advancement of the world of education. However, this technology-based education is still experiencing various obstacles and challenges. For example, remote areas that still lack the introduction of digital technology and networks so that there are delays in the development of technology-based education.